War after the war - Choy, Natalie Ching Mun (2019)
War after the War​ is a journalism feature writing package that explores the long lasting effects of the Vietnam War in Quang Tri, a central Vietnamese province which saw one of the fiercest battles from November 1955 to April 1975. We chose Quang Tri because it was one of the worst-hit areas during the war. The US military sprayed two million litres of poisonous herbicide Agent Orange ​(General Statistics Office of Viet Nam, 2016) ​and contaminated more than 83 percent of the province with unexploded bombs (Quang Tri Mine Action Centre, 2010) War does not end when bombs stop falling and peace treaties are signed. Our work seeks to shed light on the consequences of war faced by the people of Quang Tri today. Many young Vietnamese, most who had not been born during the war, suffer from severe health conditions caused by Agent Orange. The unexploded wartime bombs continue to be a threat to safety, with deaths and injuries reported yearly. War after the War​ explores whether local and international aid have been sufficient and effective and also looks into the controversies surrounding the healthcare system for Agent Orange victims in the province. To gain a deeper sense of the current situation in Quang Tri, we travelled to the province in November 2018 to speak with villagers, families with Agent Orange victims, bomb survivors, war veterans, non-governmental organisations, local media, and the relevant experts and ministries. War after the War: Report Beyond Quang Tri, we also reached out to newsmakers regionally and internationally; mainly experts who specialise bomb defusal and Agent Orange-related health conditions, as well as organisations that provide foreign aid in the province.